Reconstructing Employee Engagement Narratives in Remote Work Cultures through Leadership Micro-Interactions - Wasiman, Wasiman (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine how leadership micro-interactions reshape the narrative of employee engagement in the context of remote work cultures. The massive shift towards hybrid and online work patterns over the past decade has challenged the conventional employee engagement model that has relied on physical interactions, organizational structures, and formal interventions from human resource management. Through a narrative qualitative approach, this study analyzed 24 in-depth interviews with employees from the technology sector and creative industries in Southeast Asia who worked remotely. The results of the thematic analysis show that employee engagement in the context of digital work is formed through the presence of micro leadership, such as informal appreciation, empathy conveyed through short messages, providing contextual feedback, and quick responses to emotional and work needs. This interaction, although not formal, is perceived by employees as an indicator of attention, recognition, and psychological presence from the boss. These findings confirm that attachment in remote work culture is formed through narrative mechanisms born from consistent and meaningful micro-relational experiences. The study concludes that in the era of remote work, the role of leaders shifts from managers of structures to facilitators of meaning and emotional connection. This research contributes to the development of engagement theory by emphasizing the importance of micro and contextual approaches in building authentic working relationships, as well as providing practical implications for organizations in designing relevant engagement strategies in the ever-evolving digital work ecosystem.